PENGARUH PERSEPSI DUKUNGAN ORGANISASI, WORK LIFE BALANCE, DAN KEPEMIMPINAN TERHADAP KOMITMEN ORGANISASI - Dwi Ani Rahayu (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study purpose to examine the influence of perceptions of organizational support, work-life balance, and leadership on organizational commitment in Kampung Marketindo Berdaya located in Purbalingga. This type of research is quantitative to examine the influence between variables. The study population was 451 commercial employees, while the research sample was 110 employees. Research determined through the slovin formula, a sample technique used simple random sampling, this research analysis technique uses SmartPLS. The results found that the perception of organizational support has a significant positive effect on organizational commitment, work-life balance has a positive but not significant influence on organizational commitment , and leadership has a significant positive effect on organizational commitment. From this, it can be concluded that the perception of organizational support and leadership holds the most control in increasing organizational commitment.